2013
DOI: 10.1037/a0031864
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating fidelity to the wraparound service model for youth: Application of item response theory to the Wraparound Fidelity Index.

Abstract: The wraparound process is a mechanism for multi-system planning and care coordination for youth with serious emotional and behavioral problems. Fidelity monitoring is critical to effective implementation of evidence-based practices in children’s mental health, as it helps ensure that complex interventions like wraparound are implemented as intended. The 40-item Wraparound Fidelity Index, version 4 (WFI-4; Bruns, Burchard, Suter, Leverentz-Brady, & Force, 2004) is the most frequently used measure of fidelity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Each item is related to one of the 10 principles of wraparound; e.g., “Does the team evaluate progress toward the goals of the plan at every team meeting?” (Outcome-based). Total scale alpha coefficients of .88 and .92 and test-retest reliabilities of .84 and .88 have been found for the caregiver and facilitator forms, respectively (Bruns et al, 2004, 2008; Pullmann, Bruns, & Sather, 2013). Support for validity is found in correlations with alternative fidelity measures (see below); and ability to discriminate between wraparound and other interventions, (Bruns et al, 2006; 2008; Pullmann et al, 2013).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Each item is related to one of the 10 principles of wraparound; e.g., “Does the team evaluate progress toward the goals of the plan at every team meeting?” (Outcome-based). Total scale alpha coefficients of .88 and .92 and test-retest reliabilities of .84 and .88 have been found for the caregiver and facilitator forms, respectively (Bruns et al, 2004, 2008; Pullmann, Bruns, & Sather, 2013). Support for validity is found in correlations with alternative fidelity measures (see below); and ability to discriminate between wraparound and other interventions, (Bruns et al, 2006; 2008; Pullmann et al, 2013).…”
Section: Methodsmentioning
confidence: 93%
“…To assess fidelity, caregivers and providers (facilitators and case managers) in both groups were interviewed using the Wraparound Fidelity Index, version 4 (WFI-4) (Bruns et al, 2004, 2005, 2008; Pullmann, Bruns, & Sather, 2013). The WFI is a measure of adherence to the principles of the wraparound process.…”
Section: Methodsmentioning
confidence: 99%
“…For the current study, only the WFI-4 caregiver total scores were used as they were the most readily available across these sites, and previous studies have shown the highest variability in caregiver WFI-4 scores compared to other respondents (Pullmann et al, 2013). For the 47 sites that had TOM and WFI-4 data, 918 teams had TOM administrations and WFI-4 interviews were conducted with caregivers on 1,098 teams.…”
Section: Procedures and Resultsmentioning
confidence: 99%
“…Specifically, previous research has found that wraparound fidelity measures that rely on staff, parent, and youth report of implementation content and process can be susceptible to limited variation and “ceiling effects” that reduce utility of the tools and compromise psychometrics (Bruns et al, 2004; Pullmann, Bruns, & Sather, 2013). As an alternative or complement to interview or self-report, independent, direct observation methods can provide a rich account of behaviors and interactions of interest that reduces bias from treatment expectancy or overestimation (Aspland & Gardner, 2003; Eames et al, 2008; Webster-Stratton & Hancock, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, IRT analysis can also be used for evaluating construct validity of a scale. Rasch model for dichotomous data [10] and Rasch model for polytomous responses, called Partial Credit Model [11], were usually applied to evaluate dimensional structure and construct validity of a certain scale [12][13][14]. IRT Graded Response Model (GRM) [15], which was especially for the ordered polytomous response, can also be used for construct evaluation and item selection through evaluating the estimated test information and item psychometric parameters [16,17].…”
Section: Introductionmentioning
confidence: 99%